Sustainable development of Vehicular Fog Computing Using Karlskrona Manifesto - Inam Ul Haq (NUML International Journal of Engineering and Computing)
The emerging concept of smart cities, smart vehicles and smart traffic systems using Vehicular Fog Computing (VFC) technology is based on the concept of cloud and edge computing which assist in the automation and implementation of such smart concepts. But implementing and utilizing Vehicular Fog Computing (VFC) will need an excessive amount of power for the communication and decision-making system and will also lead to cause a huge amount of electromagnetic radiation. The sustainable and environmentfriendly development and implementation of such systems and infrastructure is still a key challenge for the industry. This research article undergoes a thorough sustainability analysis of the proposed system using the Karlskrona manifesto, which helped us to identify the current and future viable goals and aim of the system and their order of impact on the individuals. Society and economy. The development of The Sustainability and Analysis diagram(SusAD) explored the immediate, intermediate, and structural impact of technical, individual, social, environmental and economic dimensions of the system, this research article also proposes alternative ways to achieve sustainability and prevent the adverse effects of the system implementation.